2020
DOI: 10.1002/acm2.13084
|View full text |Cite
|
Sign up to set email alerts
|

Contextual loss based artifact removal method on CBCT image

Abstract: Purpose: Cone beam computed tomography (CBCT) offers advantages such as high ray utilization rate, the same spatial resolution within and between slices, and high precision. It is one of the most actively studied topics in international computed tomography (CT) research. However, its application is hindered owing to scatter artifacts. This paper proposes a novel scatter artifact removal algorithm that is based on a convolutional neural network (CNN), where contextual loss is employed as the loss function. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 34 publications
(66 reference statements)
1
20
0
Order By: Relevance
“…The most objective comparisons of image quality can be found in studies that compare multiple architectures or correction techniques for generating sCT images using the same datasets. 18,19,27,35,39,41,44,47,49,57,60,61,63 Where DL methods were compared to classical CBCT correction methods, Barateau et al 61 demonstrated that their GAN sCT achieved a lower MAE than DIR of the CT (82.4 ± 10.6 vs. 95.5 ± 21.2 HU), which was found to be consistent with the results in Thummerer et al (36.3 ± 6.2 vs. 44.3 ± 6.1 HU). 57 Similarly in Liang et al, 39 cycle-GAN showed improved image qual-ity metrics over DIR of the CT when a saline-adjustable phantom was used in a controlled experiment.…”
Section: Network Architecturessupporting
confidence: 71%
See 4 more Smart Citations
“…The most objective comparisons of image quality can be found in studies that compare multiple architectures or correction techniques for generating sCT images using the same datasets. 18,19,27,35,39,41,44,47,49,57,60,61,63 Where DL methods were compared to classical CBCT correction methods, Barateau et al 61 demonstrated that their GAN sCT achieved a lower MAE than DIR of the CT (82.4 ± 10.6 vs. 95.5 ± 21.2 HU), which was found to be consistent with the results in Thummerer et al (36.3 ± 6.2 vs. 44.3 ± 6.1 HU). 57 Similarly in Liang et al, 39 cycle-GAN showed improved image qual-ity metrics over DIR of the CT when a saline-adjustable phantom was used in a controlled experiment.…”
Section: Network Architecturessupporting
confidence: 71%
“…Augmentation of training data is a strategy used to synthetically increase the number of examples to prevent overfitting to the specific variance of the training set and improve model generalizability. The most popular augmentation techniques were random horizontal flips, 18,27,37,42,44,48,55,57,60 followed by random rotations 15,18,44,60,61,63 . The addition of noise, 18,36,46 translational shifts, 55,57,61 random crops, 37,42,44 random shears, 15,61 and scaling 15 were also utilized in the literature.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations